Opioid Overdose: Risk Assessment and Mitigation in Outpatient Treatment. Issue 6 (November 2016) - Lin, Lewei Allison; Hosanagar, Avinash; Park, Tae Woo; Bohnert, Amy S.B.
Abstract : The present clinical case discussion focuses on a patient with comorbid substance use disorder (SUD) and chronic pain, who experienced an overdose of heroin. The case illustrates the complex array of risk factors that contribute to overdose risk, discusses the use of naloxone, and highlights the need for further risk mitigation interventions in patients at risk for overdose.